Do socio-demographic characteristics affect graduates’ employment status? - Jafrin, Nusrat; Ghosh, Deboshree; Saif, Abu Naser Mohammad (Springer Nature, 2025)
Despite having a demographic dividend, the unemployment rate is soaring in Bangladesh, posing a great challenge for the nation. This perplexing situation demands knowledge of socio-demographic factors that may affect the employment status among graduates. Thus, this study aims to examine the impact of socio-demographic factors, such as gender, age, marital status, field of study, and family financial support on employment status. To achieve this objective, a questionnaire survey was conducted. Through the survey, data were collected from 415 respondents and analyzed using a Forward Likelihood Ratio binary logistic regression. The findings revealed that age, marital status, field of study, and financial support are crucial predictors that affect the probability of employment among graduates, whereas gender does not influence the probability of getting employed. The insights of the current study will assist policymakers in reaping the demographic dividend to reduce graduate unemployment by incorporating sociodemographic characteristics in Bangladesh’s policymaking for graduates. This study will help the government meet its commitment to development goals by identifying the basic socio-demographic elements that influence graduates’ employment status.